(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In modern clinical practice, laboratory parameters play a key role in assessing a patient’s condition, predicting the course of disease, and selecting optimal treatment strategies. The dynamics of laboratory markers make it possible not only to detect pathological changes at early stages but also to objectively evaluate the effectiveness of ongoing therapy and the risk of developing complications. Of particular prognostic significance are indicators of inflammation, hemostasis, metabolic status, liver and kidney function, as well as immunological and biochemical markers. Comprehensive analysis of laboratory data in combination with clinical and instrumental examination methods contributes to improved prognostic accuracy, personalization of treatment, and better disease outcomes. The use of advanced laboratory technologies expands the possibilities for early diagnosis and monitoring of pathological processes, making laboratory parameters an essential tool of evidence based medicine.